P128 Effect of acute exercise on stress and working memory following sleep restriction. (9th November 2022) - Wallace-Webb, J; Michiel, C; Service, T; Watkinson, O; Harding, D; Mulligan, G; Stuart-Hill, L
Abstract: Introduction: Cognitive impairment poses a serious risk to worker safety. We investigated the interacting effects of acute exercise and sleep restriction (SR) on stress and working memory (WM). Methods: Our randomized crossover design had 14 adults (10 M, 23 ± 3 years) complete two sessions under different sleep conditions (normal sleep (NS)=8h; restricted sleep (RS)=4h). Sleep duration was verified by validated wrist-worn actigraphy (Fitbit tracker). Salivary cortisol levels (stress indicator) and WM (via n-back task performance) were measured before and after high-intensity exercise on a cycle ergometer. Data was collected at the same time of day for each participant and a washout interval of at least 72-hours separated experimental conditions. Results: A two-factor repeated measure ANOVA revealed sleep condition to have a significant effect on cortisol levels (F(1, 13)=7.78, p<0.05) and n-back reaction time (RT) (F(1, 13) = 10.54, p<0.01), but not response accuracy. Post-hoc dependent t-tests showed that RS lead to slower RTs compared to the NS condition (t(27)=3.32, p<0.01), as well as higher cortisol levels both before (t(13)=2.22, p<0.05) and after (t(13)=2.64, p<0.05) exercise. Acute exercise did not affect cortisol levels, but did appear to have a facilitative effect on response accuracy (t(27)=2.13, p<0.05), as well as RT in both sleep conditions ( ES: t(13)=2.32, p<0.05. RS: t(13)=2.2, p<0.05). Discussion: These findings suggest that RS may lead to increased stress and impaired cognitive function, while acute exercise may serve as an effective tool for counteracting the negative cognitive effects induced by SR.